KONTRIBUSI PEMIKIRAN JANE DAMMEN MCAULIFFE TERHADAP KERUKUNAN ANTAR UMAT BERAGAMA - Iwanebel, Fejrian Yazdajird (UIN Sunan Kalijaga Yogyakarta, 2014)
This article discusses Jane Dammen Mcauliffe, an orientalist. He was one of the orientalist who was keen to study of Qur’an. His interest rest on religiosities issues, especially about the views of Islam on Christians. The conclusions derived from this article, the study of the appreciation of Qur’an on Christians that has been done by Mcauliffe in his works, at least provide a new view that Qur’an substantially do not discredit the religious groups outside of Islam. This perspective, in the context of the relationship between religions, is very important to be voiced. With that kind of junderstanding, the interpretation on Qur’an will be able to transform from exclusivity to inclusivity. Thus, al-Qur’an is no longer made as the legitimacy by certain groups to attack other groups.